2022
DOI: 10.19027/jai.21.2.142-151
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of fermented rice bran to replace soybean meal in the diet of Clarias sp. fingerling

Abstract: Rice bran is being fermented using Aspergillus niger in order to increase its usage as a raw material for the catfish diet. This research aims to evaluate the potentials of rice bran fermented with A. niger to replace soybean meal in catfish Clarias sp diet. There were two research stages, first the fermentation test of A. niger on rice bran that used a completely randomized factorial design consisting of 2 factors, namely the dose of A. niger (0, 0.5, 1, 1.5, and 2 g/100 g) and incubation time (0. 24 and 48 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 36 publications
3
4
0
Order By: Relevance
“…The fermentation process of A. niger is believed to have reduced the crude fiber value and anti-nutritional content in the leaves. This aligns with the statement by Putra et al (2022a) that the fermentation of feed ingredients using A. niger can decrease the crude fiber value and anti-nutritional substances. However, in the present study, the authors did not measure the anti-nutritional substances in Moringa leaf extract before and after fermentation.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The fermentation process of A. niger is believed to have reduced the crude fiber value and anti-nutritional content in the leaves. This aligns with the statement by Putra et al (2022a) that the fermentation of feed ingredients using A. niger can decrease the crude fiber value and anti-nutritional substances. However, in the present study, the authors did not measure the anti-nutritional substances in Moringa leaf extract before and after fermentation.…”
Section: Discussionsupporting
confidence: 89%
“…Fermentation process using Aspergillus niger Tiegh. can reduce the crude fiber and anti-nutritional content in fish feed ingredients (Putra et al 2022a). Several studies have reported natural potential sources of carotenoid to improve the color quality of goldfish such as astaxanthin (Weeratunge and Perera 2016), red paprika (Kumar et al 2017), bixin (Dananjaya et al 2017), Lutein (Besen et al 2019), annatto seeds extract (Dananjaya et al 2020), red yam flour (Putra and Romdhonah 2019), carrot flour (Tiewsoh et al 2019), lobster meal (Bell et al 2019), Spirulina platensis (Gomont) Geitler (Kargun and Dikbas 2020), sweet potato and yellow pumpkin flour (Kautsar et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…This indicates that fermentation could improve the nutritional value of rice bran and be used as a partial replacement for soybean meal in the diet of P. monodon. The results of this study also showed higher replacement levels of FRB when compared to another study where only 20% of soybean meal was replaced by FRB utilizing A. niger in catfish diets (Putra et al, 2022). Other studies have also reported the positive effects of replacing soybean meal with fermented agro-industrial wastes on shrimp growth.…”
Section: Discussionsupporting
confidence: 59%
“…The quantity of total amino acids in FRB was also increased as compared to the unfermented rice bran, indicating an improvement in the quality of protein. Similar improvements in the protein content and amino acid profile were observed when rice bran was fermented using A. niger (Putra et al, 2022). The beneficial effect of SSF was also reported in fermented copra meal (Dairo and Fasuyi, 2008), fermented sweet potato meal (Traifalgar et al, 2019), and fermented rice bran (Joseph et al, 2008).…”
Section: Discussionsupporting
confidence: 53%
“…Soybean and rapeseed and oil cakes submitted to SSF using R. oryzae, A. ibericus, and A. niger reduced acid detergent fiber (ADF) by about 67-69%, and neutral detergent fiber (NDF) by about 53-63% due to the production of carbohydrases [16]. Similarly, the SSF of rice bran with A. niger decreased ADF and NDF by 28% and 18%, respectively [47].…”
Section: Discussionmentioning
confidence: 99%